2015
DOI: 10.1007/s10840-015-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Venous hemostasis postcatheter ablation of atrial fibrillation while under therapeutic levels of oral and intravenous anticoagulation

Abstract: Immediate hemostasis of the femoral venous access sites after insertion of multiple sheaths for AF ablation in the presence of anticoagulation can be safely and effectively achieved using the F-8 suture technique. This technique helps minimize the period of inadequate anticoagulation immediately following ablation and shortens the time required to achieve adequate hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 18 publications
2
38
1
Order By: Relevance
“…8- 10 Although the time to immediate hemostasis was shorter and the proportion of patients requiring protamine was lower in the FoE suture groups, the incidence of vascular complications was similar between the groups owing to the low frequency of complications. 8-10 Thus, we set rebleeding after leaving the electrophysiology laboratory as one of the primary endpoints to evaluate the efficacy.…”
Section: Conflict Of Interestmentioning
confidence: 95%
See 1 more Smart Citation
“…8- 10 Although the time to immediate hemostasis was shorter and the proportion of patients requiring protamine was lower in the FoE suture groups, the incidence of vascular complications was similar between the groups owing to the low frequency of complications. 8-10 Thus, we set rebleeding after leaving the electrophysiology laboratory as one of the primary endpoints to evaluate the efficacy.…”
Section: Conflict Of Interestmentioning
confidence: 95%
“…10 Previous studies have reported the efficacy of the FoE suture to achieve hemostasis without increasing puncture site complications and to possibly shorten the duration of bed rest. Therefore, we evaluated hemostasis following RFCA using a simple protocol: hemostasis of 3 femoral sheaths with 2 FoE sutures followed by a short duration of bed rest (4 h) in patients undergoing RFCA for AF.…”
mentioning
confidence: 99%
“…F8S have been shown to be equally safe and effective as MC after AF ablation, with a low rate of complication . In addition, we recently showed that F8S can significantly reduce recovery time in the EP laboratory.…”
Section: Discussionmentioning
confidence: 92%
“…Manual compression (MC) after sheath removal to achieve postprocedure venous hemostasis has been the traditional standard; however, suture techniques, such as the figure‐of‐eight sutures (F8S), are now widely used as an alternative. F8S has been shown to be equally effective and safe as MC, but it does have some disadvantages . Suture knots can fragment when cut and can be difficult to remove.…”
Section: Introductionmentioning
confidence: 99%
“…In the patients treated with non-vitamin K antagonist oral anticoagulants, the last dose was administered 24 h before the procedure, and the therapy was reintroduced up to 6 h after the procedure. Antithrombotic treatment with heparin was conducted in accordance with the typical scheme, with the monitoring of activated clotting tine, without reversing the effect of heparin at the end of the procedure [4,5]. …”
Section: Methodsmentioning
confidence: 99%